The bad things we do because of empathy. (3rd April 2018) - Breithaupt, Fritz
ABSTRACT: Empathy is usually seen as a prosocial and morally positive influence on behaviour. This article provides an overview of cases of negative acts motivated by empathy. It includes discussions of polarizations that are fueled by side-taking and empathy, selfish forms of empathy (such as sadistic empathy, vampirism, and helicopter parenting), and filtered empathy (using identification with a third person as a medium to have empathy with another). The definition of empathy used is to co-experience the situation of another.